The Regional Development of Borderlands : an Explorative Study in the Franco-Italian Alps - Schelde, B.; Hoekyeld, G. (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1992)
Despite the important influence borders have on the development of borderlands, regional geography does not have a theory on this influence. In this paper, the authors implement Fischer's theory on regional development in the framework of a study of four municipalities in the Franco-Italian Alps. The authors point out that the effect of the border depends on the capability of regional Systems to cross the border. This capability in itself depends on the characteristics of the border. Furthermore the authors point at the importance of the way local actors adapt to external stimuli.After a brief overview of the development of the French municipalities of Briançon and Modane and the Italian municipalities of Susa and Bardonècchia, the hypotheses are tested.Recognizing the necessity of more refined studies on the subject the authors conclude that Fischer's theory is a very valuable one in the study of borderlands.